Understanding pore water pressure responses to sulphate in cemented tailings backfill with superplasticizers under thermo-hydro-mechanical-chemical field conditions - Zubaida Al-Moselly; Mamadou Fall (Journal of Rock Mechanics and Geotechnical Engineering)
This research examines the impact of sulphate on pore water pressure (PWP) development in cement paste backfill (CPB) containing polycarboxylate ether (PES) superplasticizers under thermal-hydraulic-mechanical-chemical (THMC) conditions that imitate actual field curing scenarios. PWP in CPB-PES, with and without sulphate, was assessed under non-isothermal field curing temperatures, varied drainage conditions, and curing stresses using a specially experimental setup. Key findings indicate that PWP behavior in CPB with PES under field conditions diverges markedly from standard laboratory conditions due to the significant effects of field curing temperatures, drainage conditions, and backfill self-weight. The study establishes that high sulphate ion concentrations notably increase initial PWP and slow its dissipation by interfering with the cement hydration process. This interference delays hydration, reduces pore water consumption, and lowers capillary pressure. Moreover, the results show that THMC conditions, especially non-isothermal field temperatures and varied drainage scenarios, considerably accelerate cement hydration compared to standard laboratory conditions, resulting in a more rapid decrease in PWP. Furthermore, improved drainage under THMC conditions mitigates the adverse effects of sulphates by facilitating sulphate ion removal, thus supporting more efficient cement hydration and CPB self-desiccation. The insights gained from this research are essential for understanding PWP behavior in sulphate-bearing CPB-PES in the field, developing predictive THMC models for backfill performance assessment, and enhancing the safety and effectiveness of mining backfills.